Y682G Mutation of Amyloid Precursor Protein Promotes Endo-Lysosomal Dysfunction by Disrupting APP–SorLA Interaction - La Rosa, Luca Rosario; Perrone, Lorena; Nielsen, Morten Schallburg; Calissano, Pietro; Andersen, Olav Michael; Matrone, Carmela (Frontiers in Cellular Neuroscience, 2015)
The intracellular transport and localization of amyloid precursor protein (APP) are critical determinants of APP processing and β-amyloid peptide production, thus crucially important for the pathophysiology of Alzheimer’s disease (AD). Notably, the C-terminal Y682ENPTY687 domain of APP binds to specific adaptors controlling APP trafficking and sorting in neurons. Mutation on the Y682 residue to glycine (Y682G) leads to altered APP sorting in hippocampal neurons that favors its accumulation in intracellular compartments and the release of soluble APPα. Such alterations induce premature aging and learning and cognitive deficits in APP Y682G mutant mice (APPYG/YG). Here, we report that Y682G mutation affects formation of the APP complex with sortilin-related receptor (SorLA), resulting in endo-lysosomal dysfunctions and neuronal degeneration. Moreover, disruption of the APP/SorLA complex changes the trafficking pathway of SorLA, with its consequent increase in secretion outside neurons. Mutations in the SorLA gene are a prognostic factor in AD, and increases in SorLA levels in cerebrospinal fluid are predictive of AD in humans. These results might open new possibilities in comprehending the role played by SorLA in its interaction with APP and in the progression of neuronal degeneration. In addition, they further underline the crucial role played by Y682 residue in controlling APP trafficking in neurons.